Utilization and Determinants of Antenatal Care Visits in East African Countries: A Multicountry Analysis of Demographic and Health Surveys - Zemenu Tadesse Tessema; Amare Minyihun (Advances in Public Health)
Background. The health care a woman receives during pregnancy is important for her survival and baby, both at the time of delivery and shortly after that. In the context of high maternal morbidity and mortality in sub-Saharan Africa, fewer than 80% of pregnant women receive antenatal care visit services. Receiving antenatal care visits at least four times increases the likelihood of receiving effective maternal health interventions through the antenatal period. This study aimed to identify the utilization and determinants of attending at least four visits in 12 East African countries. Methods. The study used the demographic and health survey data from 12 East African countries from 2008 to 2018. The DHS program adopts standardized methods involving uniform questionnaires, manuals, and field procedures to gather information comparable across countries globally. A multivariable logistic regression model was fitted to identify the determinants of completing at least four antenatal care services. With their 95% CI obtained from the adjusted multilevel logistic regression model, the adjusted odds ratio was presented to show the magnitude of the relationship between the independent variable and completing antenatal care visits. Results. The pooled utilization of attending at least four antenatal care visit in the East African region was 52.44% (95% CI: 52.13, 52.74), with the highest attending at least four or more antenatal care visit visits in Zimbabwe (75.72%) and the lowest attending at least four or more antenatal care visit visits in Ethiopia (31.82%). The significant determinants of completing at least four ANC visits were age category (24–34 (AOR = 1.24, 95% CI: 1.18, 1.31) and 35–49 (AOR = 1.42, 95% CI: 1.32, 1.53)); being married women (AOR = 1.11, 95% CI: 1.1.05, 1.16); education levels of primary education (AOR = 1.20, 95% CI: 1.13, 1.27), secondary education (AOR = 1.24, 95% CI: 1.24, 1.47), and higher education (AOR = 1.91, 95% CI: 1.62, 2.14); birth order (2–4 (AOR = 0.75, 95% CI: 0.70, 0.79) and 5+ (AOR = 0.63, 95% CI: 0.58, 0.68)); planned pregnancy (AOR = 0.81, 95% CI: 0.75, 0.86); contraceptive utilization (AOR = 1.36, 95% CI: 1.29, 1.43); wealth status of middle (AOR = 1.11, 95% CI: 1.05, 1.17) and rich (AOR = 1.25, 95% CI: 1.18, 1.32); having no problem accessing health care (AOR = 1.0.95, 95% CI: 0.89, 0.97); and living countries. Conclusions. The coverage of completing the recommended antenatal care visit was low in the region. Age, marital status, mother’s and partner’s education, women’s occupation, birth order, planned pregnancy, contraceptive utilization, wealth status, healthcare accessibility, and living countries were the major determinants of completing recommended antenatal care visits. Therefore, intersectoral collaboration to promote female education and empowerment, improve geographical access to health care, and strengthen implementation of antenatal care policies with active community participation is recommended. In addition, creating a conducive environment in entrepreneurial activities for poor women is needed.